2020
DOI: 10.1021/acsearthspacechem.0c00048
|View full text |Cite
|
Sign up to set email alerts
|

Production of Peroxy Radicals from the Photochemical Reaction of Fatty Acids at the Air–Water Interface

Abstract: Peroxy radicals are known for their role in tropospheric photochemistry as intermediates in the oxidation of volatile organic compounds, leading to the formation of ozone and organic nitrate compounds. Similarly, in the particle phase, peroxy radicals, considered a type of reactive organic species (ROS), are also involved in many chemical transformations and produce a consequential fraction of aerosols with an impact on health. Here, we show that peroxy radicals are efficiently produced at the air/water interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Oxidation kinetics of proxy aerosol samples have been well studied, 95 commonly using ozone, 24,38,96 OH radicals 55,64,97–100 photosensitization 53,101–103 or nitrate radicals 104–107 as the oxidants. In the study presented here, films of aerosol extract formed at the air–water interface were oxidized through exposure to gas-phase OH radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation kinetics of proxy aerosol samples have been well studied, 95 commonly using ozone, 24,38,96 OH radicals 55,64,97–100 photosensitization 53,101–103 or nitrate radicals 104–107 as the oxidants. In the study presented here, films of aerosol extract formed at the air–water interface were oxidized through exposure to gas-phase OH radicals.…”
Section: Resultsmentioning
confidence: 99%
“…In scenarios for investigating the degradation of these organic pollutants by direct photodegradation and by • OH oxidation, when TBA is used as the • OH scavenger, secondary ROO • will be generated and may participate in the reactions with organic pollutants. The role of secondary ROO • in the degradation and transformation of organic pollutants should not be ignored, because ROO • plays a significant role in the oxidation of volatile organic compounds . Thus, owing to the oxidation of organic pollutants by ROO • , the oxidative roles of • OH in aqueous redox reactions cannot be examined simply by comparison of the results with and without TBA.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…The role of secondary ROO • in the degradation and transformation of organic pollutants should not be ignored, because ROO • plays a significant role in the oxidation of volatile organic compounds. 39 Thus, owing to the oxidation of organic pollutants by ROO • , the oxidative roles of • OH in aqueous redox reactions cannot be examined simply by comparison of the results with and without TBA. It is alarming that TBA cannot terminate the oxidative activity of • OH.…”
Section: ■ Environmental Implicationsmentioning
confidence: 99%
“…The reaction proceeded through excitation of nonanoic acid to a triplet state, 423 which can form at the surface but not in the bulk because of the high concentration of nonanoic acid molecules required. 422 Hayeck et al 424 later showed that peroxy radicals form as reactive intermediates at the air–water interface when nonanoic acid films are directly irradiated. The mechanism for the photochemical reactions of nonanoic acid is shown in Scheme 1.…”
Section: Photochemistrymentioning
confidence: 99%